Konsep Diri Pada Mahasiswi Jilboobers - Indrawati, Ariesta; , Aad Satria Permadi, S.Psi, MA (2016)
SELF CONCEPT THE STUDENTS JILBOOBERS Ariesta Indrawati Aad Satria Permadi, S.Psi, MA Faculty Psychology University Muhammadiyah Surakarta ABSTRACT The phenomenon of the use of veil was familiar for the indonesia including for college students, one reason the use of veil to close of privacy, but not a muslim women who uses veil for adhering to fashion is a trend.It was made some women muslim using veil but still showed some the body as the chest and butt, people often called fenomana it as jilboob.This report aims to understand self concept the students jilboobers, carried on 6 the college student.Methods used in research is a qualitative methodology by approach fenomenologis.The research carried out the results the concept on girls jilboobers divided into two are self concept positive and negative self concept. Self concept influenced by internal and external factors .Internal factors affecting self concept positive penilaian-penilaian of individuals about himself , inidvidu consider themselves to be having a pattern good communication with or to others , individual by self concept positive can receive himself .Besides however there are some external factors affecting the formation of self concept is the responses from people about individuals , the environmental influences .Individual by self concept positive accept informasi-informasi of others either positive or negative to him. The formation of self concept negatively affected by assumption of about yourself , individual consider themselves to be less having a pattern good communication with or to others .Individual by self concept negative less willing to receive negative information to him .External factors can also affect the formation of self concept negative , external factors affecting the formation of self concept the negative comments and promiscuity environment .Environment can make a big difference for the establishment of self concept and interact with the environment individual will be penilaian-penilaian people about individuals. Keyword : Veil, Jilboob, Self-Concept